An examination of potential mediators of the relationship between polygenic scores of BMI and waist circumference and phenotypic adiposity. Issue 9 (1st September 2020) - Stephan, Yannick; Sutin, Angelina R.; Luchetti, Martina; Caille, Pauline; Terracciano, Antonio
Abstract: Objective : The present study examined whether physical activity, personality, cognition, education, and depressive symptoms mediate the association between polygenic scores (PGS) for body mass index (BMI) and waist circumference and the corresponding phenotypic adiposity measures. Design : Participants were 9, 139 individuals aged 50 to 107 years (57% women; Mean Age: 68.17, SD: 10.06) from the Health and Retirement Study who were genotyped. Trained staff measured their height, weight, and waist circumference, and participants answered questions on physical activity, personality, education, cognitive function, and depressive symptoms. Main Outcome Measures: BMI and waist circumference. Results: A higher PGS for both BMI and waist circumference were related to higher phenotypic BMI and waist circumference, respectively, in part through their association with lower physical activity, conscientiousness, education, and higher depressive symptoms but not cognition. The mediators accounted for 6.6% of the association between PGS and BMI and 9.6% of the association between PGS and waist circumference. Conclusion: The present study provides new evidence on the multiple, distinct pathways through which genetic propensity to higher BMI and waist circumference may lead to higher adiposity in adulthood. Individuals with a higher genetic predisposition to obesity may gain more weight through less adaptive behavioral, personality and educational profiles.